Scandal proof : do ethics laws make government ethical? - Mackenzie, G. Calvin (Brookings Institution Press, 2002)
"In 1961, President John F. Kennedy signed Executive Order 10930, the first step in a long series of efforts to regulate the ethical behavior of executive branch officials. A few years later Lyndon B. Johnson required all senior officials to report assets and sources of nongovernment income to the Civil Service Commission. The reaction to Watergate opened the floodgates to more laws and rules: the Ethics in Government Act of 1978, subsequent expansions of that act in the 1980s and 1990s, and sweeping executive orders by Presidents George H.W. Bush and Bill Clinton." "The consequence of these aggressive efforts to scandal proof the federal government is a heavy accumulation of law and regulation administered by agencies employing hundreds of people and spending millions of dollars every year. Ethics regulation has been one of the steady growth sectors in the federal government for decades." "This book explores the process that led to the current state of ethics regulation in the federal executive branch. It assesses whether efforts to scandal proof the federal government have been successful, what they have cost, and whether reforms should be considered."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Political ethics -- United States.; Civil service ethics -- United States.; Conflict of interests -- United States.; Executive departments -- United States.; Morale politique -- États-Unis.; Fonctionnaires -- Déontologie -- États-Unis.; Conflits d'intérêts -- États-Unis.; POLITICAL SCIENCE -- General.; POLITICAL SCIENCE -- Public Affairs & Administration.; Civil service ethics; Conflict of interests; Executive departments; Political ethics; United States